Good and Bad Lies in "The Adventures of Huckleberry Finn" by Mark Twain - Osowská, Zuzana (Univerzita Pardubice, 2011)
This Bachelor Thesis deals with the identification and description of lies in the novel, The Adventures of Huckleberry Finn, by Mark Twain. The beginning discusses the definition of a lie from a dictionary and from the Bible. Then an example from the Bible is used to confirm that even in such a sacred thing as the Bible, lies are in the stories therefore, displaying that lies can be found anywhere. The thesis goes on to identify the various lies that appear in the novel. Each lie has an explanation to the situation at hand and explains the situation the character of the lie is in. There is emphasis on the main character Huckleberry Finn, who throughout the entire novel provides many insights, opinions and contemplations on scenarios and situations in the story. Along with the lies, there is some analysis of the characters that appear during Huck?s adventure. Towards the end of the paper, the lies are categorized into vicious, childish, innocuous and noble. The main focus of this Bachelor Thesis is to state if all lies are considered bad, why are some meant well, why do some help others or hurt them and if they have positive outcomes.
Dobré a špatné lži v Dobrodružství Huckleberryho Finna od Marka Twaina
Keywords: Huckleberry Finn; lži; náboženství; Jim; vévoda; nejstarší syn královský; zlomyslné; dětinské; neškodné; ušlechtilé; lies; Jim; Duke and Dauphin; religion; noble; vicious; innocuous; childish